The Unheard Voices in Pashto Women Poetry - Momand, Ahmad Gul; Firky, Zabihullah (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2022)
Pashto women have not written their poetry with enough exposer to their untold world which could have been parallel to their men counterparts. Futher, it appears that Pashto women poets never tried to be parallel with their men counterparts. Instead, they choose to think and speak for their wishes, cries, thoughts, pains, and joys. In Pashto women poetry, we read a lot about their pain and pleas for justice, status, and rights. Women poets have provided details about them in their poetry with oriented thoughts. Much of their subjects for their poetry is nationalism, love, pace, education and moral man. This article will study women poetry and will bring out their themes of their poetry.